PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN REKAM MEDIS ELEKTRONIK TERHADAP KEAKURATAN DATA - Firzatul Khalisha; Khoirunnisa; Rumaisha Assyifa; Sri Hajijah Purba (CV. ADIBA ADISHA AMIRA, 2025)
The implementation of Electronic Medical Record Management Information System (EMMRE) has become an innovative solution in improving the efficiency and accuracy of medical record data, which is an important element in clinical and operational decision making. This study aims to analyze the effect of the implementation of EMMRE on data accuracy based on a literature review of various previous studies. The research method used is a literature review approach by reviewing articles from relevant national and international journals, using keywords such as